Penerapan Terapi Relaksasi Benson Untuk Menurunkan Intensitas Nyeri Pada Pasien POST Operasi Laparotomy Di Ruang HCU Cempaka Rumah Sakit Umum Daerah (RSUD) DR. Moewardi Surakarta - Annisa Annisa; Eska Dwi Prajayanti; Isti Wulandari (Lembaga Pengembangan Kinerja Dosen, 2024)
Surgery is an invasive treatment that involves opening a part of the body through an incision which ends with closing or suturing the wound. Molecular mechanisms for treating pain have led to the development of multimodal analgesia, combining pharmacological and non-pharmacological interventions. Benson Relaksası is a development of the deep breathing relaxation method by involving the patient's key factors which can create a calm environment. To find out the results of applying Benson relaxation therapy to reduce pain intensity in post laparotomy patients at HCU Cempaka Regional General Hospital (RSUD) Dr. Moewardi Surakarta. This type of research is descriptive research in the form of a case study. Involving 2 post-operative patients. The research instrument used the Numeric Rating Scale (NRS) questionnaire. The results of the study showed that before applying Benson relaxation therapy to Mr. M, an NRS score of 7 (severe pain) was obtained, while for Mrs. Trn.M obtained an NRS score of 3, indicating both patients experienced mild pain after the intervention. After applying benson relaxation for 3 consecutive days on Mr. M and Mrs. H, it can be concluded that there was a decrease in the level of pain in both patients.